Synthetic lubricants an application for oleochemicals. - PORIM International Palm Oil Conference. Progress, Prospects Challenges Towards the 21st Century. Chemistry and Technology Septembe 9-14 : Kuala Lumpur, Malaysia : 49398. (Kuala Lumpur : PORIM, 1993)
3 ref.